Iraq : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper discusses the need to reduce Iraq's current expenditure to create fiscal space for inclusive growth. Iraq's public spending is high in international comparison and is driven by its two largest components: compensation of public employees and social transfers. The reform of social welfare cash transfer programs promises to improve their large targeting errors and result in greater capacity to address poverty at a lower fiscal cost. The government also needs to introduce further amendments to the draft pension bill and critically review programs benefiting victims of war and political persecution to improve their targeting and limit their potential for abuse and a negative impact on the labor supply.